2008
DOI: 10.1038/ncponc1242
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcoma of the breast following surgery and radiotherapy for breast cancer

Abstract: Breast angiosarcoma following surgery and radiotherapy for breast cancer is a rare but important clinical entity. This article reviews all published cases and includes data on incidence, etiology, presentation, diagnosis, management and prognosis. Breast angiosarcoma remains challenging clinically, radiologically and histologically, and thus a high index of suspicion is required in susceptible patients. Surgery is the primary treatment option and there are an increasing number of studies on the use of radiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 78 publications
2
67
0
3
Order By: Relevance
“…8 The median latency period ranges from 59 to 103 months in the literature, which is in line with our data. 8,[24][25][26][27][28] RAS may be of any type, but angiosarcoma was the most common in our patient group and in other series of thoracic RAS. [2][3][4]19,22 Angiosarcoma may be associated with chronic lymphedema of a limb or of the chest wall (Stewart-Treves [ST] syndrome), which is diagnosed most frequently after axillary lymph node dissection as a part of breast cancer treatment and can occur in the lymphedematous arm itself or in the shoulder, axillary, or chest wall region.…”
Section: Discussionmentioning
confidence: 55%
“…8 The median latency period ranges from 59 to 103 months in the literature, which is in line with our data. 8,[24][25][26][27][28] RAS may be of any type, but angiosarcoma was the most common in our patient group and in other series of thoracic RAS. [2][3][4]19,22 Angiosarcoma may be associated with chronic lymphedema of a limb or of the chest wall (Stewart-Treves [ST] syndrome), which is diagnosed most frequently after axillary lymph node dissection as a part of breast cancer treatment and can occur in the lymphedematous arm itself or in the shoulder, axillary, or chest wall region.…”
Section: Discussionmentioning
confidence: 55%
“…Vascular endothelial growth factor (VEGF) is a potent mediator of angiogenesis, and thus may play an important role in the development and progression of angiosarcoma. Studies have suggested involvement of the VEGFR system in the growth and proliferation of hemangiosarcoma cells in vitro (5). Furthermore, it has been reported that positive immunohistochemical staining for VEGF occurs in 14% of primary angiosarcomas and of its 3 known receptors, VEGFR3 has been shown to be present in 50% of all angiosarcomas (5).…”
Section: Discussionmentioning
confidence: 99%
“…Primary angiosarcomas of the breast generally occur between the ages of 20-40 years and are rare, with an incidence of less than 0.0005% (10). These constitute less than 0.01% of all breast cancers (4,5). Following review of published cases on the subject, Abbott and Palmieri (5) noted that secondary angiosarcomas following mastectomy and radiotherapy presented at a median age of 67 years with a median latency of 72 months between radiotherapy and angiosarcoma development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations